Knowledge translation in health and wellness research focusing on immigrants in Canada - Tanvir C. Turin; Mohammad Ali Ashraf Lasker; Nahid Rumana; Marcus Vaska; Mohammad Z. I. Chowdhury; Jessica Naidu; Nashit Chowdhury (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONKnowledge translation (KT) is a relatively new concept referring to transfers of knowledge into practice in collaboration with multiple sectors that work for the health and wellness of society. Knowledge translation is crucial to identifying and addressing the health needs of immigrants. AIMTo scope the evidence on KT research engaging immigrants in the host country regarding the health and wellness of immigrants. METHODSThis study followed a scoping review approach suggested by Arksey O'Malley. We identified relevant studies from both academic and grey literature using structured criteria, charted the data from the selected studies, collated, summarised and report the results. RESULTSAnalysis of the eligible studies found two types of KT research: integrated KT and end-of-grant KT. Meeting or discussion with community-level knowledge-users were common KT activities among immigrants, but they were involved in the entire research process only if they were hired as members of research teams. Most KT research among immigrants explored cancer screening and used a community-based participatory action research approach. Barriers and enablers usually came from researchers rather than from the community. There was little practice of evaluation and defined frameworks to conduct KT research among immigrants in Canada. CONCLUSIONThis study can help the researchers and other stakeholders of health and wellness of the immigrant population to identify appropriate KT research activities for immigrants and where KT research is required to facilitate the transfer of research knowledge into action.